Environmental assessment of livestock systems with the emergy methodology. Efficiency of extensive livestock systems in harsh environments - Vigne, Mathieu (Perspective, 2014)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"The livestock sector will need to provide meat and milk for a growing population, while at the same time limiting its environmental impacts. To meet this challenge, more and more studies are being conducted to identify the most efficient systems from an environmental perspective, especially those that use the fewest nonrenewable resources in relation to their output. In 2006, an FAO report thus called attention not only to the environmental damage they cause, but also to the lack of efficiency of livestock systems, especially extensive systems in developing countries, whose level of food production remains low. Questioning this report, a recent study conducted by CIRAD in four different regions shows that extensive dairy systems in Mali can be more efficient than intensive systems in Reunion Island, and just as efficient as semi-intensive systems in western France. This result was obtained using the emergy methodology, which uses one type of unit to evaluate all the resources consumed to generate food or non-food products. This methodology takes into account the complex and multifunctional nature of livestock systems, especially extensive ones. Emergy could be a useful tool enabling decision-makers to develop livestock policies adapted to suit individual contexts, and to thereby meet the growing demand for livestock products."" data-sheets-userformat=""2":585,"3":[null,0],"6":"1":["1":2,"2":0,"5":[null,2,0],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"12":0">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"The livestock sector will need to provide meat and milk for a growing population, while at the same time limiting its environmental impacts. To meet this challenge, more and more studies are being conducted to identify the most efficient systems from an environmental perspective, especially those that use the fewest nonrenewable resources in relation to their output. In 2006, an FAO report thus called attention not only to the environmental damage they cause, but also to the lack of efficiency of livestock systems, especially extensive systems in developing countries, whose level of food production remains low. Questioning this report, a recent study conducted by CIRAD in four different regions shows that extensive dairy systems in Mali can be more efficient than intensive systems in Reunion Island, and just as efficient as semi-intensive systems in western France. This result was obtained using the emergy methodology, which uses one type of unit to evaluate all the resources consumed to generate food or non-food products. This methodology takes into account the complex and multifunctional nature of livestock systems, especially extensive ones. Emergy could be a useful tool enabling decision-makers to develop livestock policies adapted to suit individual contexts, and to thereby meet the growing demand for livestock products."" data-sheets-userformat=""2":585,"3":[null,0],"6":"1":["1":2,"2":0,"5":[null,2,0],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"12":0">The livestock sector will need to provide meat and milk for a growing population, while at the same time limiting its environmental impacts. To meet this challenge, more and more studies are being conducted to identify the most efficient systems from an environmental perspective, especially those that use the fewest nonrenewable resources in relation to their output. In 2006, an FAO report thus called attention not only to the environmental damage they cause, but also to the lack of efficiency of livestock systems, especially extensive systems in developing countries, whose level of food production remains low. Questioning this report, a recent study conducted by CIRAD in four different regions shows that extensive dairy systems in Mali can be more efficient than intensive systems in Reunion Island, and just as efficient as semi-intensive systems in western France. This result was obtained using the emergy methodology, which uses one type of unit to evaluate all the resources consumed to generate food or non-food products. This methodology takes into account the complex and multifunctional nature of livestock systems, especially extensive ones. Emergy could be a useful tool enabling decision-makers to develop livestock policies adapted to suit individual contexts, and to thereby meet the growing demand for livestock products.